HUBUNGAN PELATIHAN DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT PERMATA KELUARGA LIPPO CIKARANG - Alex H; Christina Natalina; Ramot P Simanjuntak (Buletin Ekonomi, 2023)
This study aims to determine the relationship between training and compensation to employee performance at the Permata Keluarga Hospital Lippo Cikarang. Research Methodology uses a quantitative approach. The population and samples in this study were all employees of the Permata Keluarga Lippo Cikarang Hospital which amounted to 46 people. The data collection technique used is a literature study and through a questionnaire with likert scale measurements. Data analysis in this study used the help of software SPSS version 26. The results of the study by probability test (sig) showed that the training variable on employee performance at the Permata Keluarga Lippo Cikarang Hospital was significantly related because 0.000<0.05 (sig<0.05) so that Ho was denied Ha was accepted, the variable of compensation for employee performance at the Permata Keluarga Hospital Lippo Cikarang was significantly related because of 0.000<0.05 (sig <0.05) so that Ho was rejected and Ha was accepted and the training variable with compensation for employee performance at Lippo Cikarang Family Gem Hospital was significantly related because of 0.000<0.05 (sig<0.05) so That Ho was rejected and Ha was accepted. Keywords: Training, Compensation, Employee Performance